“The show must go on”: How Paralympic athletes safeguarded their mental well-being and motivation to train for the postponed Tokyo 2020 games - Van Biesen, Debbie; Morbee, Sofie (Frontiers in Psychology, 2023)
Introduction After the decision to postpone the Tokyo 2020 Games due to the COVID-19 pandemic, athletes had to adjust to a novel situation with feelings of uncertainty and insecurity. Grounded in Self-Determination Theory, this study was the first to examine whether different motivational profiles among Paralympic athletes can be identified, and to link these profiles with the athletes’ emotional, cognitive, and performance-related outcomes in times of a pandemic. Methods Five months before the start of the Paralympic Games, the participants (N = 32; mean age = 33.2 ± 6.8 years) completed an online questionnaire measuring their demographics, basic psychological needs, perceived stress, depressive symptoms, general well-being, and motivational self-regulation strategies. Two months after the Games, they completed a second online questionnaire measuring their actual and perceived performance at the past Games. Results Through K-means cluster analysis, three distinct clusters were identified based on the athletes’ dominant type of motivation, these are, dominantly amotivated (n = 11), autonomously motivated (n = 12), and controlled motivated (n = 9). Comparisons of athletes’ emotional, cognitive, and performance-related outcomes depending on their motivational profile revealed that the athletes with a dominantly amotivated profile had the least adaptive outcomes (i.e., low need satisfaction, high need frustration, and more depressive symptoms). Athletes with a dominantly autonomously motivated profile made less use of controlling self-motivating strategies compared to the other two profiles. Moreover, their actual performance at the Paralympic Games was better. Discussion Although none of the athletes were at severe risk for depression or showed extremely high levels of stress, these results confirm that improving the quality of athletes’ motivation can safeguard their well-being and enhance performance in Paralympic Sports.